Expectations versus fundamentals: Does the cause of banking panics matter for prudential policy? - Todd Keister; Vijay Narasiman (Federal Reserve Bank of New York, 2011)
There is a longstanding debate about whether banking panics and other financial crises always have fundamental causes or are sometimes the result of self-fulfilling beliefs. Disagreement on this point would seem to present a serious obstacle to designing policies that promote financial stability. However, we show that the appropriate choice of policy is invariant to the underlying cause of banking panics in some situations. In our model, the anticipation of being bailed out in the event of a crisis distorts the incentives of financial institutions and their investors. Two policies that aim to correct this distortion are compared: restricting policymakers from engaging in bailouts, and allowing bailouts but taxing the short-term liabilities of financial institutions. We find that the latter policy yields higher equilibrium welfare regardless of whether panics are sometimes caused by self-fulfilling beliefs.
Keywords: E61; G21; G28; 330; banking panics; financial regulation; bailouts